Nilai Tambah dan Kelayakan Usaha Pengolahan Kopi Arabika pada Unit Usaha Produktif Ulian Murni Kabupaten Bangli - NI LUH WICANODIAN SURYA; I MADE SUDARMA; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Value Added and Feasibility of Business Processing Arabica Coffee on Productive Business Unit Ulian Murni Bangli Regency Ulian Murni Productive Business Unit is Arabica coffee processing business that had been generated value added and obtained the assistance of investment by Department of Estate Crops Bali Province such as processing facilities, and credit. This study aimed to analyze the value added, financial feasibility, and business obstacles in Ulian Murni Productive Business Unit. Value added was calculated by Hayami method, and financial feasibility was analyzed by investment criteria. The results show that value added of raw materials are Rp 2,548.16/kg from HS coffee processing, Rp 2,429.06/kg from 250 grams packaging of coffee powder and Rp 1,032.22/kg from 200 grams packaging. Based on investment criteria, Ulian Murni was financially feasible with Rp 3,324,980,784.49 of Net Present Value; of Internal Rate of Return equals to 36.81%; Net Benefit Cost Ratio of 3.25; and Payback Period at 5.62 years. The results of sensitivity analysis show that the business is prone toboth on product prices decrease by 16.10% and operating costs increased by 20.20%. Business obstacles faced by Ulian Murni were the length of sunlight for coffee processing, lack of product promotion, and limited of human resources for coffee powder processing. Keyword: Arabica coffee, added value, financial analysis, business constraints.